Internet connectivity disruption in Cambodia (Cambodia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Cambodia. Data sourced from IODA.
Network Disruption Incident ID: KH-2026-0110. Severity: critical. Confidence: 70%